Synthesis of nanoporous type A and X zeolite mixtures from biomass combustion fly ash for post-combustion carbon capture - Petrovic, Ben; Gorbounov, Mikhail; Özmen, Seran; Clough, Peter T.; Soltani, Salman Masoudi (Institute of Electrical and Electronics Engineers (IEEE), 2022)
In this study, improved nanoporous zeolites for use in post-combustion carbon capture have been synthesised from industrial-grade biomass combustion fly ash generated in one of the largest biomass combustion power plants in the UK. The method of nanoporous zeolite synthesis follows an alkaline fusion-assisted hydrothermal procedure. The nanoporous zeolites have been characterised by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR). The presence of two crystalline structures, Faujasite and Linde Type A has been confirmed by the characterisation results. The CO 2 adsorption investigations were conducted via thermogravimetric analysis (TGA) to estimate the uptake capacity of the prepared adsorbents. TGA studies suggest that the improved nanoporous adsorbent, evaluated under 100 mol % CO 2 at atmospheric pressure, has an equilibrium capacity of over 1.6 mmolCO 2 /g at 50°C, a two-fold increase from our previous study with a crystalline structure confirmed by XRD.